Amphiregulin as a central dynamic network biomarker in inhaled polyhexamethylene guanidine triggered pulmonary fibrosis - Jianzhong Zhang; Xin Li; Yuxin Ma; Wanjun Zhang; Zihao Han; Yanting Li; Jiayin Sun; Siqi Wang; Wei Han; Jing Liu; Yuxin Zheng; Jinglong Tang (Journal of Hazardous Materials, 2026)

Study on shear strength prediction model of glass fiber-improved loess in seasonal frozen regions based on POA-XGBoost - Xiyue Wang; Wanjun Ye; Qianqian Ma; Hao Yang; Minghao Zhang (Cold Regions Science and Technology, 2026)

Molecular characterization of a novel hadakavirus from Pestalotiopsis mangiferae - Qihua Wang; Mengyi Chen; Quansheng Yao; Xiaowei Ma; Feng liu; Jingbo Wu; Xi Zhu; Yu Zhang; Xidan Pang; Guohui Zhang; Wanjun Liao (Archives of Virology, 2026)

Dynamics of greenhouse gas emissions and methanogenic communities in sludge treatment wetlands: responses to intermittent loading - Junyu Liang; Yubo Cui; Kedong Ma; Xu Ma; Wanjun Zhang; Ruijie Tian; Yang Wang; Hongxuan Qi (Ecological Engineering, 2026)

A Transition Model for Spontaneous Capillary Liquid–Liquid Imbibition of Carreau–Yasuda Fluids in Straight Circular Tubes - Pengyu Fu; Yuhang Wang; Wanjun Lu; Hao Ma; Yongqing Cao; Huirong Guo (Transport in Porous Media, 2026)

An improved stochastic finite-fault simulation method and its application to large magnitude thrust earthquakes - Wanjun Ma; Zhinan Xie (Earthquake Engineering and Engineering Vibration, 2026)

Key odorants driving aroma transformation during aging process in Liubao tea: A sensory and chemical perspective - Ying Yang; Ruijin Qiu; Qiushuang You; Wanjun Ma; Yuhui Zhang; Yan Zhao; Gaozhong Yang; Yue Zhang; Zhi Lin; Yin Zhu; Haipeng Lv (Food Chemistry, 2025)

Whether aristolochic acid directly drives hepatocarcinogenesis: comprehensive investigations from mutational signatures to animal models - Lu Yang; Wanjun Lin; Meina Shi; Zifeng Huang; Xuening Zhang; Yanchao Yang; Tong Chu; Dayuan Zheng; Dongfan Yang; Wenzhe Ma (Archives of Toxicology, 2025)

Experimental Study on the Damage Characteristics of Sandstone Under Freeze‒Thaw Loading Coupling via the Acoustic Emission Method - Wanjun Ye; Zhiyuan Xu; Qianqian Ma; Jiahao Wang; Yuntao Wu (Rock Mechanics and Rock Engineering, 2025)

Species discrimination of Fritillaria Bulbus using PCR-CRISPR/Cas12a-based nucleic acid detection - Dongfan Yang; Yanchao Yang; Wanjun Lin; Meina Shi; Zifeng Huang; Xuening Zhang; Wenzhe Ma (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Revealing the mechanisms of water permeability enhancement of urban loess subgrades due to vibration application - Kuan Liu; Wanjun Ye; Xueyang Sun; Faning Dang; Mingming He; Zhao Duan; Jianquan Ma; Jingjing Nan; Ruihui Zheng; Quanjiu Wang (Transportation Geotechnics, 2024)

Novel cow dung-doped sludge biochar as an efficient ozone catalyst: Synergy between graphitic structure and defects induces free radical pathways - Yuxuan Yang; Kedong Ma; Yubo Cui; Ke Zhao; Yuning Lu; Wanjun Zhang; Peijing Kuang; Xuejun Zou (Environmental Research, 2024)

Atmospheric VOCs in an industrial coking facility and the surrounding area: Characteristics, spatial distribution and source apportionment - Meicheng Wen; Weiqiang Deng; Jin Huang; Shu Zhang; Qinhao Lin; Chao Wang; Shengtao Ma; Wanjun Wang; Xin Zhang; Guiying Li; Taicheng An (Journal of Environmental Sciences, 2024)

A Novel Platinum Resistance-Related Immune Gene Signature for Overall Survival Prediction in Patients with Ovarian Cancer - Chenfei Zhou; Junnan Ma; Wanjun Luo; Jiemei Hu; Jing Chen; Suiying Liang; Shanyang He (Biochemical Genetics, 2024)
Ovarian cancer (OV) is a highly heterogeneous gynecological tumor that makes the prognostic prediction challenging. Resistance to platinum-based chemotherapy is associated with a poor prognosis in OV. There seems to be an overlap between molecular mechanisms responsible for platinum resistance and immunogenicity in OV. However, the predictive role of platinum resistance-related immune genes for OV prognosis needs to be further explored. In our study, the mRNA expression data of OV patients with corresponding clinical information were collected from The Cancer Genome Atlas (TCGA) cohort and International Cancer Genome Consortium (ICGC) cohort. A multigene signature was constructed for OV patients in the TCGA cohort using the least absolute shrinkage and selection operator (LASSO) Cox regression model according to the optimal value of λ and was validated in the ICGC cohort. Furthermore, we performed functional analysis to explore the immune status between low- and high-risk groups based on the median value of the risk score for the multigene signature. Our data showed that there were 41.1% of the platinum resistance-related genes which differentially expressed between immune score low- and high-OV patients in the TCGA cohort. Univariate Cox regression analysis identified 30 differentially expressed genes (DEGs) associated with overall survival (OS) ( P P

Corrigendum to “Aroma characterisation of Liu-pao tea based on volatile fingerprint and aroma wheel using SBSE-GC-MS” [Food Chem. 414 (2023) 135739] - Wanjun Ma; Yin Zhu; Shicheng Ma; Jiang Shi; Han Yan; Zhi Lin; Haipeng Lv (Food Chemistry, 2023)

Atmospheric occurrences and health risk assessment of polycyclic aromatic hydrocarbons and their derivatives in a typical coking facility and surrounding areas - Weiqiang Deng; Meicheng Wen; Chao Wang; Jin Huang; Shu Zhang; Shengtao Ma; Jukun Xiong; Wanjun Wang; Xin Zhang; Taicheng An (Chemosphere, 2023)

Simulation of the 2022 Mw 6.6 Luding, China, earthquake by a stochastic finite-fault model with a nonstationary phase - Pengfei Dang; Jie Cui; Wanjun Ma; Yadong Li (Soil Dynamics and Earthquake Engineering, 2023)

Novel Ag-bridged dual Z-scheme g-C3N4/BiOI/AgI plasmonic heterojunction: Exceptional photocatalytic activity towards tetracycline and the mechanism insight - Wenxia Wang; Zhen Li; Kailin Wu; Guodong Dai; Qingping Chen; Lihua Zhou; Junxia Zheng; Liang Ma; Guiying Li; Wanjun Wang; Taicheng An (Journal of Environmental Sciences, 2023)

Mapping local climate zones for cities: A large review - Fan Huang; Sida Jiang; Wenfeng Zhan; Benjamin Bechtel; Zihan Liu; Matthias Demuzere; Yuan Huang; Yong Xu; Lei Ma; Wanjun Xia; Jinling Quan; Lu Jiang; et al. (Remote Sensing of Environment, 2023)

Aroma characterisation of Liu-pao tea based on volatile fingerprint and aroma wheel using SBSE-GC–MS - Wanjun Ma; Yin Zhu; Shicheng Ma; Jiang Shi; Han Yan; Zhi Lin; Haipeng Lv (Food Chemistry, 2023)

Distribution, Source Apportionment, and Health Risk Assessment of Heavy Metals in Groundwater in a Multi-mineral Resource Area, North China - Wanjun Jiang; Hongwei Liu; Yizhi Sheng; Zhen Ma; Jing Zhang; Futian Liu; Sheming Chen; Qinghua Meng; Yaonan Bai (Exposure and Health, 2022)

Groundwater quality assessment and hydrogeochemical processes in typical watersheds in Zhangjiakou region, northern China - Wanjun Jiang; Yizhi Sheng; Hongwei Liu; Zhen Ma; Yaxin Song; Futian Liu; Sheming Chen (Environmental Science and Pollution Research, 2022)

Involvement of ROS/NLRP3 Inflammasome Signaling Pathway in Doxorubicin-Induced Cardiotoxicity - Shanshan Wei; Wanjun Ma; Xiaohui Li; Chuanhao Jiang; Taoli Sun; Yuanjian Li; Bikui Zhang; Wenqun Li (Cardiovascular Toxicology, 2020)

GABAergic Abnormalities Associated with Sensorimotor Cortico-striatal Community Structural Deficits in ErbB4 Knockout Mice and First-Episode Treatment-Naïve Patients with Schizophrenia - Chengcheng Zhang; Peiyan Ni; Yikang Liu; Yang Tian; Jinxue Wei; Bo Xiang; Liansheng Zhao; Xiaojing Li; Xiaohong Ma; Wei Deng; Wanjun Guo; Rongjun Ni; et al. (Neuroscience Bulletin, 2020)

Interaction Between Variations in Dopamine D2 and Serotonin 2A Receptor is Associated with Short-Term Response to Antipsychotics in Schizophrenia - Liansheng Zhao; Huijuan Wang; Yamin Zhang; Jinxue Wei; Peiyan Ni; Hongyan Ren; Gang Li; Qiang Wang; Gavin P Reynolds; Weihua Yue; Wei Deng; Hao Yan; et al. (Neuroscience Bulletin, 2019)

Age-Related Reduction in Cortical Thickness in First-Episode Treatment-Naïve Patients with Schizophrenia - Yin Lin; Mingli Li; Yi Zhou; Wei Deng; Xiaohong Ma; Qiang Wang; Wanjun Guo; Yinfei Li; Lijun Jiang; Xun Hu; Nanyin Zhang; Tao Li (Neuroscience Bulletin, 2019)

Testing the role of genetic variation of the MC4R gene in Chinese population in antipsychotic-induced metabolic disturbance - Yamin Zhang; Hongyan Ren; Qiang Wang; Wei Deng; Weihua Yue; Hao Yan; Liwen Tan; Qi Chen; Guigang Yang; Tianlan Lu; Lifang Wang; Fuquan Zhang; et al. (Science China Life Sciences, 2019)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Altered splenic miRNA expression profile in H1N1 swine influenza - Liangzong Huang; Jun Ma; Yankuo Sun; Yanli Lv; Wen Lin; Mingjie Liu; Changsong Tu; Pei Zhou; Wanjun Gu; Shuo Su; Guihong Zhang (Archives of Virology, 2015)